The coherency of ambient seismic noise recorded during land surveys and the resulting implications for the effectiveness of geophone arrays - Dean, Timothy; Dupuis, Christian; Hassan, R. (Society of Exploration Geophysics, 2015)
The use of analog sensor arrays is often assumed to provide signal-to-ambient-noise improvements proportional to the square root of the number of sensors being summed. We determined via numerical modeling and field experiments that the improvements sought were significantly hindered once the ambient noise exhibited coherence over the array being summed. As a first step, a numerical model was developed to explore the optimal sensor spacing based on the average correlation coefficient between sensors. Field experiments were then carried out to measure ambient noise using closely spaced geophones at several sites in Perth, Western Australia. We show that the measured noise at six test sites was strongly coherent over distances of up to 10 m, with the level of coherency being inversely proportional to frequency. The resulting optimum geophone spacing under our field conditions was determined to be 7.5 m. These results offered further encouragement to reassess our use of analog arrays and to consider recording the output from individual sensors. In addition to the benefits from postacquisition noise suppression, this approach will enable increased trace density without degradation of the signal caused by strong coherent noise sources over acquisition spreads.